PENINGKATAN KINERJA PEMASARAN UMKM KABUPATEN PURBALINGGA MELALUI PEMANFAATAN STRATEGI DIGITAL MARKETING - Hana Afifah; Juli Handayani; Hasirun Hasirun; Muhammad Reza Setiawan Setiawan; Melia Dwi Renovriska; Titi Safitri Maharani (ICON Publisher, 2025)
This community service activity aims to improve the marketing performance of MSMEs in Purbalingga Regency through the use of digital marketing strategies. The background to this activity is based on the low level of understanding and ability of business actors in using digital media as a means of promotion and business communication. The implementation method is carried out through training, mentoring, and evaluation of the practice of using social media as a marketing tool. The results of the activity show a significant increase in the ability of participants to manage digital promotional content, interact with consumers, and optimize market reach. MSMEs also began to show changes in marketing behavior that are more adaptive to technological developments and modern consumer behavior. These findings confirm that digital transformation is a strategic factor in strengthening the competitiveness and sustainability of small businesses in the digital economy era. The activity's limitations lie in the relatively short duration of mentoring and the limited technological resources owned by the participants. Nevertheless, this activity provides theoretical and practical contributions to the development of a community-based training model relevant to strengthening the digital capacity of MSMEs in semi-urban areas such as Purbalingga.